Evaluate \( 6 u^{2} v^{3} \) when \( u=-\frac{2}{3} \) and \( v=-\frac{1}{2} \)
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Bonus Knowledge
To evaluate \( 6 u^{2} v^{3} \) when \( u=-\frac{2}{3} \) and \( v=-\frac{1}{2} \), we start by calculating \( u^{2} \) and \( v^{3} \). First, compute \( u^{2} \): \[ u^{2} = \left(-\frac{2}{3}\right)^{2} = \frac{4}{9} \] Next, compute \( v^{3} \): \[ v^{3} = \left(-\frac{1}{2}\right)^{3} = -\frac{1}{8} \] Now substitute \( u^{2} \) and \( v^{3} \) into the expression \( 6 u^{2} v^{3} \): \[ 6 u^{2} v^{3} = 6 \left(\frac{4}{9}\right) \left(-\frac{1}{8}\right) \] Calculating this step by step: \[ 6 \cdot \frac{4}{9} = \frac{24}{9} = \frac{8}{3} \] Now, multiplying by \( -\frac{1}{8} \): \[ \frac{8}{3} \cdot \left(-\frac{1}{8}\right) = -\frac{8}{24} = -\frac{1}{3} \] So, the final result is: \[ \boxed{-\frac{1}{3}} \]